ALCOHOLIC EXTRACTS OF INSECTICIDAL PLANTS IN THE MANAGEMENT OF Bemisia tabaci BIOTYPE B IN TOMATO CROPS - Diego Miguel Blanco Bertolo; Luciana Cláudia Toscano; José Augusto dos Santos Rodrigues; Ítalo Ferreira Vetruve; Gustavo Davanzo Ballera (Revista de Agricultura Neotropical, 2025)
This study aimed to evaluate the effectiveness of alcoholic extracts in managing Bemisia tabaci biotype B in tomato crops. The experiments were conducted at UEMS - Cassilândia, using a randomized block design with five treatments and four replications. Alcoholic extracts were obtained from Ruta graveolens, Mentha pulegium, Tagetes erecta, and Allium sativum. Both choice and no-choice tests were performed. The parameters evaluated included attractiveness, oviposition non-preference, and nymph mortality. The choice test observed adult repellency for T. erecta and R. graveolens. These same extracts also resulted in fewer eggs, indicating oviposition non-preference. R. graveolens, T. erecta, and A. sativum extracts exhibited the highest nymph mortality. In the no-choice test, R. graveolens and T. erecta continued to show the lowest oviposition preference. Again, the extracts of R. graveolens, T. erecta, and A. sativum increased nymph mortality. It was concluded that the extracts of R. graveolens and T. erecta negatively affected B. tabaci populations, particularly regarding repellency, inhibition of oviposition, and nymph mortality. These extracts demonstrated over 80% efficacy only in the choice test.